2014
DOI: 10.12983/ijsres-2014-p0094-0106
|View full text |Cite
|
Sign up to set email alerts
|

Trends on Natural Organic Matter in Drinking Water Sources and its Treatment

Abstract: Abstract. Natural organic matter (NOM) can be defined as a mixture of complex organic compounds that universally present in natural waters. High NOM content in water strongly impact the water quality and treatment in several ways (e.g. causing colour and odour, filter fouling and increase coagulant dose). Besides that, NOM also acts as the main precursor to disinfectant by products (DBPs) produce from the reaction of NOM and disinfectant during water treatment. DBPs are known to be carcinogenic to human and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
(80 reference statements)
2
16
0
2
Order By: Relevance
“…3a). These results are in agreement with previous reports that surface water NOM consists of about 50% of HPO while the hydrophilic fraction contribution ranges from 25-40%, and the transphilic fraction occupies the remainder (Universiti et al, 2016). The WTP reduced the hydrophobic fraction from 45% content in raw water to 36% in final water.…”
Section: Polarity Fractionation Dynamics Along the Treatment Trainsupporting
confidence: 93%
See 1 more Smart Citation
“…3a). These results are in agreement with previous reports that surface water NOM consists of about 50% of HPO while the hydrophilic fraction contribution ranges from 25-40%, and the transphilic fraction occupies the remainder (Universiti et al, 2016). The WTP reduced the hydrophobic fraction from 45% content in raw water to 36% in final water.…”
Section: Polarity Fractionation Dynamics Along the Treatment Trainsupporting
confidence: 93%
“…Fluorescence spectroscopy is a robust tool for characterizing fluorescent dissolved organic matter (FDOM) in various natural and engineered aquatic systems (Baghoth et al, 2010;Sanchez et al, 2013;Tijani et al, 2014;Zhang et al, 2015). Owing to simplicity in application, FEEM spectroscopy has promise in predicting the removal of NOM during both conventional and advanced drinking water treatment processes (Kastl et al, 2016;Wang and Benjamin, 2016;Li and Hur, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the application of Fe2(SO4)3 is more economical due to higher removal of turbidity at lower dosage, however higher turbidity removal can be expected with higher dosage of FeCl3. According to a study by Ibrahim and Aziz [14], overdosing the coagulant results in a substantial increase in the amount of generated sludge and a decrease in pH. This might explain the decreases in removal after 80 mg/L for all cases when applying Fe2(SO4)3 as coagulant.…”
Section: Resultsmentioning
confidence: 97%
“…The groundwater site was selected with prior knowledge from Akbar [14] that it contained higher NOM compared to usual groundwater. This was to allow the maximum THM formation potential that might happen in the presence of elevated NOM levels in source water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation